PROJECT-BASED LEARNING IN LEARNING WRITING FOR UNIVERSITY LEVEL - -, Retma Sari; Maman Suryaman; Basikin (Universitas Tidar, 2023)
This research describes about the problems of writing in university level. Writing becomes a challenging and complicated skill to master. Some of components must be involved and integrated proportionally. Therefore, project-based learning is offered to solve the problems. This study purposes to explore the improvement of project-based learning in the students’ writing in the fourth semester students of the English Education Program and the students’ responses when it is implied in learning writing. Qualitative was used as a research method and classroom action research as a research design. The research sample was fourth-semester students from English Education Program in a university in Magelang, Central Java in the academic year 2022-2023. To collect the data it is using observation, test, and questionnaire then for analyzing the data is using triangulation. The result found that project-based learning is able to improve the students writing achievements. It could be seen from the increasing of the score for each cycle (writing better) and students’ positive responses during the implementation of this method from improving of students’ activeness and motivation in writing learning. So it can be stated that Project Based Learning increases mark and encouragement of students’ writing learning.